CLASSIFICATION OF ACL TEARS IN THE PEDIATRIC AND ADOLESCENT POPULATION. Issue 4 (28th April 2020) - Kushare, I; Beran, M; Klingele, K; Ettia, E; Elabd, A; Inneh, I; McKay, S
Background: There have been previous imaging classification schemes in the literature that described ACL tears in adults and pediatric patients. More recent publications have described the epidemiology, injury mechanisms, and repair versus reconstruction techniques. None have proposed an arthroscopic classification for pediatric patients. Purpose: To describe our experience with a novel arthroscopic classification using 4 patterns of ACL tears depending on the type of tear and the tissue quality. Methods: An IRB approved prospective with 2 parts to this study: Part 1: Single center prospective case series using descriptive statistics of intraoperative findings. We included children ≤18 years old with an ACL tear who underwent surgery within 8 weeks of injury. Those with associated ligamentous injuries or revision surgery were excluded. We proposed a 4-stage classification as follows: I. Avulsion off femur II. <10% tear from femoral end III. Midsubstance tear IV. Single bundle tear. Part 2: Four fellowship-trained surgeons from two tertiary children's hospitals classified ACL injury based on intraoperative video of 33 randomly selected surgeries. 2 rounds of classification were performed. Inter and intra-observer reliability studies were calculated using Kappa statistics. Results: 120 patients (73 males and 47 females) with mean age of 16 (9-20) years and mean BMI 26 (16-51) were included in this study. 59 patients (49%) had left sided injury while 61 (51%) had right sided injury. 29 (24%) patients reported contact injury while 91 (76%) reported non-contact. Isolated ACL injury was recorded in 49 patients only (41%) while concomitant injuries were recorded in 71 patients (59%). The most common associated injury was the lateral meniscus tear (33%), followed by lateral and medial meniscus tear (13.4%). According to our classification, 23 (19.2%) patients were type I, 15 (12.5%) were type II, 65 (54.2%) were type III, and 17 (14.2%) were type IV. The intra-rater reliability was excellent for 2 reviewers, good for 1 and marginal for another. The overall inter rater reliability for all 4 reviewers was marginal for both readings (k=0.35, 95% CI: 0.23-0.44; k=0.26, 95%CI: 0.16-0.35 respectively). Conclusion: With renewed interest in ACL repairs and techniques, a classification system for ACL tears can guide a proper surgical plan. Our classification system provides a step to achieve this goal. It showed overall good intra-observer reliability, with marginal inter-observer reliability.